Basic Texts in International Relations - Luard, Evan. author. aut Link
XXI, 624 p.
Keywords: This text combines passages from major writers on international relations over the ages, together with a brief commentary on each. The collection is divided into three main sections - the individual, the state and the society of states - the three main alternative ways of conceiving the subject.